Potential and mechanisms of indigenous Indonesian medicinal plants in treating sexual dysfunction: A systematic review and pharmacological network overview - Sukardiman; Roihatul Mutiah; Rosita Handayani (Heliyon)
The epidemiology of Erectile Dysfunction (ED) continues to exhibit an increasing trend annually. The use of synthetic drugs in treating ED often leads to undesirable side effects and has limited efficacy. In Indonesia, several indigenous plants have been empirically utilized for ED remediation. This study aims to identify the latest scientific evidence on the potential of native Indonesian medicinal plants for ED treatment and elucidate the underlying molecular mechanisms using a systematic review and Pharmacological Network approach. There are 12 potential plants most commonly used by ethnic groups in Indonesia to treat erectile dysfunction (ED) as reviewed in this study. A systematic review search was conducted across three databases (PubMed, Scopus, and Springer) without limiting the publication years. Article screening was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. Determination of compound target genes was carried out using GeneCards, while disease target genes were analyzed using DisGeNET. Network topology was explored with Cytoscape 3.10, and the construction of Protein-Protein Interaction Networks was realized using STRING version 12.0. GO and KEGG analyses were subsequently conducted with SRplot. The systematic review findings indicated that 12 articles met the predefined inclusion criteria. The pharmacology network analysis demonstrated that the compounds present in Eurycoma longifolia, specifically stigmasterol, eurycomanone, and eurycomalactone, target 13 genes associated with erectile dysfunction (ED), which include BCL2, AKT1, SOAT1, PCSK9, ACHE, BDNF-AS, TMX2-CTNND1, GSK3B, LINCO1672, TP53, H19, HIF1A, and IL1B. These target genes are connected to the biological mechanisms underlying steroid hormone biosynthesis, which is essential for the formation of testosterone. Therefore, Eurycoma longifolia demonstrates significant potential for development as a promising phytopharmaceutical candidate in the treatment of sexual dysfunction.